Vocational Higher Education Governance Recommendation Based On Cobit 5 Enabler Generic Model - Heru Nugroho; Kridanto Surendro (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Enterprise governance for higher education can be viewed as arrangements that include a variety of university assets in order to support the strategy in achieving the goals and objectives.  In the implementation governance in university there are factors that affect good governance which are individual or groups. These factors are then called an enabler of enterprise governance. In the previous research obtained the fact that the enabler of enterprise governance that provide significant influence in the governance of vocational higher education is the organization structure and information. Using four common dimensions for enablers in COBIT 5 Enabler Generic Model will give recommendation for governance in vocational higher education. These recommendations are expected help the vocational higher education in preparation of blue print of governance needs by considering the enablers of organizational structure and information.